MULTIPLE BASAL CELL CARCINOMAS FOLLOWING X-RAY TREATMENT FOR TINEA CAPITIS IN CHILDHOOD: A CASE REPORT AND A LITERATURE REVIEW - Cakić, Jelena; Lekić, Branislav; Maširević Mudrić, Iva; Tomanović, Marija; Popadić, Svetlana (Medical Research, 2024)
Introduction: Basal cell carcinoma (BCC) is the most frequent skin cancer with a rising incidence worldwide. Predilection sites are head and neck in 80-85% of cases. The leading risk factors are sun exposure and ionizing radiation. In the middle of the 20th century, radiation-induced epilation was used as an efficient treatment method for tinea capitis. Patient review: We report a case of an 80-year-old man with a 16-year history of the successive occurrence of multiple BCCs on the scalp, face, and neck. He also had the history of tinea capitis treated by radiotherapy during childhood. At presentation during clinical and dermoscopic examination approximately twenty-five BCCs were observed, predominantly on scalp. The most common BCC lesion was the nodular subtype, followed by the pigmented and superficial subtypes. Histopathological examination conﬁrmed the diagnosis of BCC in multiple lesions and one squamous cell carcinoma (SCC). In personal history most important comorbidity was hairy cell leukemia. The therapeutic approach was surgery and 5-fluorouracil 5% cream.Conclusion: Radiation-induced epilation was used as an efficient method for treatment of tinea capitis. One of the side effects was appearance of BCC in radiation exposed areas. Surgical excision is the gold standard for BCC treatment. Also, 5-fluorouracil 5% cream may be a good option for patients with multiple BCCs. We present satisfactory results after combined treatment in our patient.
Keywords: basal cell carcinoma; ionizing radiation; radiotherapy; tinea capitis; treatment